Proceso de atención de enfermería en paciente de 67 años de edad con insuficiencia cardiaca aguda. - Mazacon Guanoluiza, Juan Daniel (2020)
Acute Heart Failure is defined as a clinical syndrome characterized by symptoms and signs associated with abnormal heart function. This usually occurs with or without prior heart disease. The groups of people who are more likely to suffer from this pathology are the elderly, who are or are not accompanied by some other disease such as high blood pressure, diabetes, obesity and overweight. The following clinical case aims to apply a care process Nursing in a 67-year-old patient with Acute Heart Failure, in the Emergency area of the General Hospital San Francisco de Quito. A respective nursing assessment was carried out, prioritizing the signs and symptoms that the patient presented at that time, to establish the corresponding nursing care with the purpose of alleviating the problems that afflict the patient, especially improving the well-being and health of the patient. same. Through a thorough and correct nursing assessment, good results were obtained in the application of the necessary nursing care in the patient, together with the corresponding prescribed pharmacological treatment. It is very important to educate family members about the care that a patient with Acute Heart Failure should take. This respective research contributes to improving performance as nurses in a similar situation, applying appropriate nursing care in order to satisfactorily improve the health of the patient.